Pozzolanic hardened three-phase-foams. (September 2015) - Krämer, Christina; Kowald, Torsten L.; Trettin, Reinhard H.F.
Abstract: The field of lightweight materials is becoming more and more important due to the desire for material and cost savings with a simultaneous combination of thermal insulation and sustainability. It is of specific interest to obtain materials in a low density range of 60–150 kg/m 3 with high stability comparable to heavier weight materials currently in use, whilst under the constraint of reducing the content of inorganic binders. A new approach is the chemical treatment of foams based on three phases. The third phase consists of pozzolanic active nanomaterials, which can be varied and surface treated. Aided by chemical treatment of the three-phase-foams, a hardening of the foams has been achieved. Results based on studies of the microstructure and phase formation will be illustrated and discussed.